Goodyera schlechtendaliana Rchb. f. (Orchidaceae) a new angiospermic record for Bangladesh - Huda, MK; Hoque, MM (Bangladesh Journal of Botany, 2010)
Goodyera schlechtendaliana Rchb. f. of family Orchidaceae is illustrated and reported here as a new angiospermic record from Bangladesh. Key words: Goodyera schlechtendaliana; Orchid; New record; Bangladesh DOI: 10.3329/bjb.v38i2.5147 Bangladesh J. Bot. 38(2): 193-195, 2009 (December)